2016
DOI: 10.1080/09168451.2016.1171702
|View full text |Cite
|
Sign up to set email alerts
|

Production of a thermal stress resistant mutant Euglena gracilis strain using Fe-ion beam irradiation

Abstract: Euglena gracilis is a common phytoplankton species, which also has motile flagellate characteristics. Recent research and development has enabled the industrial use of E. gracilis and selective breeding of this species is expected to further expand its application. However, the production of E. gracilis nuclear mutants is difficult because of the robustness of its genome. To establish an efficient mutation induction procedure for E. gracilis, we employed Fe-ion beam irradiation in the RIKEN RI beam factory. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Reports suggest that E. gracilis exhibits polyploidy (Schiff and Epstein 1965;Hill et al 1966), which might be responsible for the observed difficulty in obtaining the nuclear genome mutants of E. gracilis (Schiff et al 1980). Although it is difficult to breed mutated E. gracilis, in the recent years, the use of heavy ion beams for inducing mutations has resulted in the appearance of mutants that exhibit previously unknown phenotypes such as tolerance to high temperature (Yamada et al 2016a) and higher lipid content (Yamada et al 2016b). Mutants generated by heavy ion irradiation are recognized as natural mutants.…”
Section: Breeding Potential Of Euglenamentioning
confidence: 99%
“…Reports suggest that E. gracilis exhibits polyploidy (Schiff and Epstein 1965;Hill et al 1966), which might be responsible for the observed difficulty in obtaining the nuclear genome mutants of E. gracilis (Schiff et al 1980). Although it is difficult to breed mutated E. gracilis, in the recent years, the use of heavy ion beams for inducing mutations has resulted in the appearance of mutants that exhibit previously unknown phenotypes such as tolerance to high temperature (Yamada et al 2016a) and higher lipid content (Yamada et al 2016b). Mutants generated by heavy ion irradiation are recognized as natural mutants.…”
Section: Breeding Potential Of Euglenamentioning
confidence: 99%
“…To improve the value of E. gracilis for industrial application, breeding methods for this species are established (Yamada et al, 2016a;Yamada et al, 2016b). Fe-ion beam irradiation efficiently induces random mutations and produces a population including various phenotypes of mutants (Yamada et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the value of E. gracilis for industrial application, breeding methods for this species are established (Yamada et al, 2016a;Yamada et al, 2016b). Fe-ion beam irradiation efficiently induces random mutations and produces a population including various phenotypes of mutants (Yamada et al, 2016b). In addition, efficient selective breeding of oil-rich E. gracilis strain is demonstrated by isolating the desired cells from the mutant pool by using fluorescence-activated cell sorting (Yamada et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…For the development of these technologies, noninvasive and safe cell viability assay 77 plays an important role as a basic technology. 78 For example, the production of nuclear mutants of E. gracilis requires a physically and 79 chemically significant load on cells due to the robustness of their genome, so it is necessary to 80 confirm whether the cells are viable or dead at screening (Yamada et al, 2016a). Moreover, 81 when the alga is mass cultured for edible use, it is necessary to confirm the state of growth.…”
mentioning
confidence: 99%